2019
DOI: 10.3389/fphys.2019.01260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Training and Isoinertial Training on Leg Extensors Muscle Function, Structure, and Intermuscular Adipose Tissue in Older Adults

Abstract: We compared the effects of aerobic high-intensity training (HIT) and isoinertial resistance training (IRT) on the strength, mass, architecture, intermuscular adipose tissue (IMAT) quality, and neuromuscular activation of the quadriceps in elderly subjects. Twelve healthy men (69.3 ± 4.2 years; 77.8 ± 10.4 kg; 1.72 ± 0.05 m) were exposed to 8 weeks of HIT (7 × 2-min cycling repetitions at 90% of trueV.O2peak, 3 times/week) and, after 4 months (detraining), to IRT (4 × 7 maximal concentric–eccentric knee extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(81 citation statements)
references
References 65 publications
1
80
0
Order By: Relevance
“…Since our results for the physiological and anthropometrical parameters obtained with HIIT have been reported and discussed elsewhere, it is sufficient here to say that they substantiate previous data showing that HIIT can improve cardiovascular performance with substantial positive effects on health-related parameters [8,10,11,[47][48][49].…”
Section: Discussionsupporting
confidence: 90%
“…Since our results for the physiological and anthropometrical parameters obtained with HIIT have been reported and discussed elsewhere, it is sufficient here to say that they substantiate previous data showing that HIIT can improve cardiovascular performance with substantial positive effects on health-related parameters [8,10,11,[47][48][49].…”
Section: Discussionsupporting
confidence: 90%
“…Of the 32 studies included, 14 were RCTs (Adamson et al, 2014 , 2020 ; Hwang et al, 2016 ; Coetsee and Terblanche, 2017 ; Sculthorpe et al, 2017 ; Aboarrage Junior et al, 2018 ; Malin et al, 2018 ; Martins et al, 2018 ; Ballesta-García et al, 2019 ; Hurst et al, 2019c ; Jiménez-García et al, 2019 ; Nunes et al, 2019 ; Taylor et al, 2019 ; Coswig et al, 2020 ), one was a quasi-experimental, non-randomized, single-blinded controlled study (Losa-Reyna et al, 2019 ), 16 were observational cohort studies (Bruseghini et al, 2015 , 2019 ; Boereboom et al, 2016 ; Guadalupe-Grau et al, 2017 ; Hayes et al, 2017 ; Herbert et al, 2017a , b ; Robinson et al, 2017 ; Wyckelsma et al, 2017 ; Andonian et al, 2018 ; Bartlett et al, 2018 ; Buckinx et al, 2018 , 2019 ; Søgaard et al, 2018 , 2019 ; Snijders et al, 2019 ), and one was a pilot study (although randomized; (Beetham et al, 2019 ) ( Table 1 ). Where a study had multiple outcome measures, they were examined separately.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to our first objective, which was to search the literature for the effect of HIIT on phenotypic characteristics of sarcopenia in older adults, we observed most studies reported at least one positive change in characteristics when compared to vs. pre-HIIT, vs. non-exercise control, or vs. MICT. In this context, 19 of 20 studies reported an improvement to ≥1 muscle function outcome for ≥1 comparisons examined (vs. pre-HIIT, vs. non-exercise control, or vs. MICT) (Bruseghini et al, 2019 ). Similarly, twelve of 22 reported an improvement to ≥1 muscle quantity outcome for ≥1 comparison examined, and 11 of 12 reported an improvement to for ≥1 physical performance outcome for ≥1 comparison examined.…”
Section: Discussionmentioning
confidence: 99%
“…As eccentric muscle strength declines with age to a lesser degree than other types of muscle strength, it may represent an effective stimulus for adaptation in older adults, playing a key role in successful ageing [ 49 , 50 , 51 ]. In particular, isoinertial resistance exercise has been suggested as a potential training modality in certain aging populations ready for higher resistance exercise stress [ 52 , 53 ], with studies mainly focusing on knee extension [ 53 , 54 , 55 ] and squat [ 56 , 57 ] exercises.…”
Section: The Undiscovered Benefits Of Isoinertial Resistance Trainmentioning
confidence: 99%
“…Flywheel knee extension trainings (8–12 weeks; 3 times/week; 7–12 repetitions; 1–4 sets per session) elicited beneficial modifications in muscle mass, strength, and architecture, and improved the quality of life and functional performances in 68-year old men [ 53 , 55 ] and the peak knee extension power in 70-year old men and women [ 54 ]. Isoinertial squat trainings (6–8 weeks; 2–3 times/week; 9–15 repetitions; 2–4 sets per session) improved mobility, balance, mean concentric propulsive velocity, and power in 65-year old men and women [ 57 ], as well as physical and functional abilities in 68-year old women [ 56 ].…”
Section: The Undiscovered Benefits Of Isoinertial Resistance Trainmentioning
confidence: 99%